2008
DOI: 10.1007/s11676-008-0010-y
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the resistance of a LEA gene from Tamarix expression in Saccharomyces cerevisiae to abiotic stresses

Abstract: The role of late embryogenesis abundant (LEA) proteins in stress tolerance was examined by using a yeast expression system.LEA protein tolerance to the abotic stresses in plants involved in salt, drought and freezing stresses and additional tolerance to heat, Na-HCO 3 (salt-alkali) and ultraviolet radiation was also investigated. The transgenic yeast harboring the Tamarix LEA gene (DQ663481) was generated under the control of inducible GAL promoter (pYES2 vector), yeast cells transformed with pYES2 empty vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…e KT1623, the yeast mutant strain, grows hardly under salt (NaCl, 1 M) and mannitol (mannitol, 0.5 M), but its resistance increased notably when overexpressing TtASR1. Similar results were found in ASR1 from rice [40] and the LEA gene from Tamarix [39]. e overexpression of TtASR1 improved E. coli cells growth under normal conditions (37°C) compared to control cells and enhanced its tolerance to high and low temperatures (4°C and 50°C).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…e KT1623, the yeast mutant strain, grows hardly under salt (NaCl, 1 M) and mannitol (mannitol, 0.5 M), but its resistance increased notably when overexpressing TtASR1. Similar results were found in ASR1 from rice [40] and the LEA gene from Tamarix [39]. e overexpression of TtASR1 improved E. coli cells growth under normal conditions (37°C) compared to control cells and enhanced its tolerance to high and low temperatures (4°C and 50°C).…”
Section: Discussionsupporting
confidence: 76%
“…In fact, yeast expression system was largely used to study the stress tolerance of some genes, for example, LEA4 gene from Brassica napus that enhanced the cellular tolerance to temperature and salt stresses of E. coli cells [38]. It was also reported that the expression of a protein gene from Porteresia coarctata (the serine-rich protein) conferred salt tolerance in yeast [39]. Heterologous expression of TtASR1 in yeast improved its growth under salt and osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…UV radiation might produce harmful thymine dimer and reactive oxygen species (ROS), numerous studies have shown that many of thymine dimers obstructed DNA replication and protein synthesis as well as uncontrolled generation of ROS could be damaging to mitochondrial and nucleic acid [28]. It has been confirmed that AtLEA5 increases the tolerance to oxidation in yeast under H 2 O 2 stress, and Tamarix LEA gene has enhanced tolerance to UV radiation in Saccharomyces cerevisiae [29,30]. The upregulation of PjLEA3 under H 2 O 2 -induced oxidative stress indicated that PjLEA3 probably can improve stress tolerance through removing ROS [13].…”
Section: Resistance To Uv Radiation Stressmentioning
confidence: 99%
“…At present, the continuous deterioration of the environment means that plants are much more likely to suffer a variety of stresses. High salinity and drought stress are major environmental factors that limit crop productivity in arid and semi-arid regions [23][24][25][26][27] . Carotenoids are essential for photosynthesis and for photoprotection.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of salt and drought on the growth of transformed E. coli BL21(DE3) cells with pET32a(+) (empty vector), and the pET32-IbPSY1 were examined every 4 h. The growth curve of the recombinant strains was compared to the control cells. To evaluate the functional significance of IbPSY1 with respect to salinity and drought stress in yeast, transformants containing pYES2-IbPSY1 and pYES2 (empty vector) were grown on SC-URA solid medium with 2% glucose and incubated for 24 h at 30 °C23 . Subsequently, a fixed number of cells from each treatment (approximately 1 × 10…”
mentioning
confidence: 99%